2013
DOI: 10.1371/journal.pone.0072524
|View full text |Cite
|
Sign up to set email alerts
|

Control of Male and Female Fertility by the Netrin Axon Guidance Genes

Abstract: The netrin axon guidance genes have previously been implicated in fertility in C. elegans and in vertebrates. Here we show that adult Drosophila lacking both netrin genes, NetA and NetB, have fertility defects in both sexes together with an inability to fly and reduced viability. NetAB females produce fertilized eggs at a much lower rate than wild type. Oocyte development and ovarian innervation are unaffected in NetAB females, and the reproductive tract appears normal. A small gene, hog, that resides in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
(86 reference statements)
0
8
0
Order By: Relevance
“…Netrin is a diffusible laminin-like protein and conserved from worms to mammals. In Drosophila , the NetAB mutants exhibit egg-laying defects due to ovulation defects in females [79]. The clathrin heavy chain gene, FRP gene (three copies) and NetAB genes could be found in the N. cucumeris genome (Additional file 1: Table S14), indicating that they perhaps function similarly in the regulation of oviposition in N. cucumeris .…”
Section: Resultsmentioning
confidence: 99%
“…Netrin is a diffusible laminin-like protein and conserved from worms to mammals. In Drosophila , the NetAB mutants exhibit egg-laying defects due to ovulation defects in females [79]. The clathrin heavy chain gene, FRP gene (three copies) and NetAB genes could be found in the N. cucumeris genome (Additional file 1: Table S14), indicating that they perhaps function similarly in the regulation of oviposition in N. cucumeris .…”
Section: Resultsmentioning
confidence: 99%
“…These findings indicated that the hmbRBC meal affects gene expression of the modulatory machinery at neural synapses. Moreover, axon guidance protein gene (AGAP008943), homologous to turtle in Drosophila (CG16857), as well as dopamine b-monooxygenase (AGAP010485) are known to be indirectly involved in oogenesis (23).…”
Section: Process Name Functionmentioning
confidence: 99%
“…94 In contrast, netrin is dispensable for cell survival, and global netrin-AB mutants have apparently wild-type egg chambers. 94,95 While this pattern of cell death does not fit the dependence receptor model, it raises the possibility that Frazzled may interact with cell death machinery by an alternate mechanism. Similarly, netrin-Neogenin signaling in the mammary gland may impinge on the cell death machinery by an as-yet-unknown mechanism.…”
Section: Guidance Pathways Regulate Mammary Gland Remodelingmentioning
confidence: 89%